Podróżować: jeździć, widzieć, myśleć - Kita, Barbara (Er(r)go. Teoria - Literatura - Kultura, 2002)
Barbara Kita "Travelling: Going, Seeing, Thinking" The author describes modern space in the light of the change in the model of travelling. The medium of television plays an important role in this practice: it mediates space and replaces its proper experience. The postmodern urban nomad (Deleuze, Maffesoli), the teleurban fliineur or the tourist-telanthrop (Berger) represent roles characteristic of a mediated perception of reality. It is the static _audiovisual vehicle" (Virilio), by introducing the spectator to a kind of inertia, that, in contact with mediated space, makes it possible for us to travel by merely seeing.